Investing in schools: capital spending, facility conditions, and student achievement (revised and edited) - Paco Martorell; Kevin Stange; Isaac McFarlin (W.E. Upjohn Institute for Employment Research, 2016)
Public investments in repairs, modernization, and construction of schools cost billions. However, little is known about the nature of school facility investments, whether such investments actually change the physical condition of public schools, and the subsequent causal impacts on student achievement. We study the achievement effects of nearly 1,400 capital campaigns initiated and financed by local school districts, comparing districts where school capital bonds were either narrowly approved or narrowly defeated by district voters. Overall, we find little evidence that school capital campaigns improve student achievement. Our event-study analyses focusing on students that attend targeted schools and therefore are exposed to major campus renovations also generate very precise zero estimates of achievement effects. Thus, locally financed school capital campaigns - the predominant method through which facility investments are made - may represent a limited tool for realizing substantial gains in student achievement or closing achievement gaps.
Keywords: I22; I24; H75; 330; School facilities; student achievement; school financing; school bonds